Factors affecting the development of takaful (Islamic insurance) system in Turkey : a mixed method study - Aslan, Hakan (My University, 2021)
Konvansiyonel sigortacılığın İslami finanstaki alternatifi olan tekafül, son yıllarda dünyada hızla gelişme göstermektedir. Tekafül sektörü her ne kadar Türkiye’de yavaş yavaş gelişse de dünya ortalamasının gerisinde kalmaktadır. Bu nedenle Türkiye’nin kendi durumunu incelemesi ve dünyanın en gelişmiş tekafül ekosistemine sahip Malezya’nın değerli tecrübelerinden ders çıkarması gerekmektedir.Bu çalışmanın amacı, Türkiye’de tekafül sisteminin gelişimini etkileyen faktörleri incelemek ve ileride daha sağlıklı bir tekafül ekosistemi için faydalı ve uygulanabilir öneriler geliştirmektir. Bu amaca ulaşmak için çalışmada karma araştırma yöntemin keşfedici sıralı deseni kullanılmıştır. Öncelikle Malezya’daki tekafül sektörünün gelişimi ile ilgili tecrübelerini aktarmak ve Türkiye için değerli tavsiyelerde bulunmaları için tekafül konusunda oldukça tecrübeli uzmanlar ile mülakat gerçekleştirilmiştir. Elde edilen nitel verilerden fenomenolojik yaklaşım ile tematik kodlar oluşturulmuş ve bu temalar bağlamında bulgular değerlendirilmiştir.Tekafül ekosisteminin kapsamlı yapısı itibariyle ilk aşamada tekafül sisteminin gelişimini etkileyen genel meseleler nitel analiz yöntemi ile alınmış ve ikinci aşamaya geçilmiştir. Bu aşamada müşterilerin tekafül ürünlerini tercih etmesini etkileyen faktörleri incelemek için nicel analiz yöntemi kullanılmıştır. Bu kapsamda, potansiyel tekafül müşterilerine anket yapılmış ve tekafül ürünlerini tercih etme niyetleri planlı davranış teorisi bağlamında ele alınmıştır.Bulgular; tekafül farkındalığı, düzenleyici ve denetleyici mekanizmaların işleyiş süreçleri, beşerî sermaye, acenteler, İslami finansa özgün sorunlar, İslami finansal yatırım araçları tekafül modelleri ile zorluklar ve beklentiler bağlamında tartışılmıştır. Daha sona tekafül sektör temsilcileri, düzenleyici ve denetleyici yapılara yönelik çeşitli politika önerileri geliştirilmiştir.Sonuç itibariyle, bu çalışma Türkiye'deki tekafül piyasasının sorunlarını teşhis etmeye ve buna bazı çareler sunmaya çalışmaktadır. Bu çalışmanın, Türkiye tekafül ekosistemine fayda sağlaması ve Türkiye tekafül sistemi konusunda yapılacak çalışmalara yol gösterebileceği düşünülmektedir.

As equivalent to the conventional insurance in the Islamic finance, takaful has been flourished all around the world in recent years. Although Turkey is developing takaful gradually, it is still far behind the world average. Therefore, it is necessary for Turkey to examine itself and learn from the treasured experiences of the most advance takaful ecosystem in the world – Malaysia.The purpose of this study is to explore the factors that impact on the development of the takaful industry in Turkey and to generate some useful and practical suggestions for a healthier takaful ecosystem in the future. This aim is achieved through a mixed method research and the exploratory sequential design is employed. Firstly, the qualitative research is done via the interviews of some highly experienced experts from Malaysia to inquire some experiences of the development of takaful market in Malaysia, and to attempt for valuable advice to Turkey with their expertise. The qualitative data is analysed with the thematic coding technique: the phenomenological perspective is adopted to create thematic codes from interviews, and the data has been interpreted according to the created themes. Since the takaful ecosystem is comprehensive and the general issues affecting its development have been identified by the qualitative analysis, this study progresses to the second stage: using the quantitative research to explore the factors influencing the purchase of takaful products from the customers. This quantitative research is implemented by distributing questionnaires to potential takaful customers and then analysed with the behavioural intention theory to comprehend the indicators impacting on their decisions to choose takaful products. The findings are discussed in several aspects, such as the public awareness, the regulatory and supervisory mechanism, the human capital, the takaful agencies, the Shariah issues, the takaful models, the Shariah compliant financial instruments, and the challenges and expectations. Meanwhile, recommendations are provided accordingly to market players, regulators, and supervisory bodies.In summary, this study strives to diagnose the problems of the takaful market in Turkey and offer some remedies to it. Hopefully, this study can benefit the Turkish takaful ecosystem and shed light upon the future studies on takaful for this country.
Keywords: Business; Insurance; Islam; Islamic Insurance; İslam; İslami Finans; İslami Sigortacılık; İşletme; Katılım Sigortacılığı Islamic Finance; Participation Insurance; Sigorta; Takaful; Tekafül; Turkey; Türkiye